Strengthening psychological resilience: the effectiveness of autogenic training of community pharmacists - Jocić, Dragana (Vojnosanitetski pregled, 2024)
Background/Aim. Psychological resilience is essential for healthcare professionals like community pharmacists. It enables them to navigate daily challenges effectively. Autogenic training (AT) has emerged as a promising psychological technique for enhancing resilience and reducing stress in this population. The aim of this study was to investigate the impact of AT on resilience among community pharmacists. Methods. The study recruited licensed pharmacists from community pharmacies. Participants received information about the aims and procedures of the research. Resilience was assessed using a scale that measured five domains: Confidence, Agility, Coping with Stress, Interpersonal Relationships, and Developmental Thinking. Using a controlled trial design, participants were randomly divided into two experimental groups, which underwent AT, and a control group, which did not undergo AT. Statistical analyses, including the Kruskal-Wallis and Wilcoxon rank-sum tests, were conducted to analyze the data. Results. Participants who underwent AT showed statistically significant improvements in resilience compared to the control group, particularly in the domains of Confidence, Coping with Stress, and Interpersonal Relationships. Furthermore, a notable shift towards higher resilience categories was observed in the experimental groups after the intervention. Conclusion. AT appears promising as an intervention to enhance resilience and reduce stress among community pharmacists. Integrating AT into pharmacist education and practice guidelines could significantly affect pharmacist welfare and patient care outcomes.
Keywords: autogenic training; community pharmacy service; pharmacists; resilience, psychological; stress psychological.